Biogas Production from Physicochemically Pretreated Grass Lawn Waste: Comparison of Different Process Schemes - Georgia Antonopoulou (Molecules, 2020)
Various pretreatment methods, such as thermal, alkaline and acid, were applied on grass lawn (GL) waste and the effect of each pretreatment method on the Biochemical Methane Potential was evaluated for two options, namely using the whole slurry resulting from pretreatment or the separate solid and liquid fractions obtained. In addition, the effect of each pretreatment on carbohydrate solubilization and lignocellulossic content fractionation (to cellulose, hemicellulose, lignin) was also evaluated. The experimental results showed that the methane yield was enhanced with alkaline pretreatment and, the higher the NaOH concentration (20 g/100 gTotal Solids (TS)), the higher was the methane yield observed (427.07 L CH4/kg Volatile Solids (VS), which was almost 25.7% higher than the BMP of the untreated GL). Comparing the BMP obtained under the two options, i.e., that of the whole pretreatment slurry with the sum of the BMPs of both fractions, it was found that direct anaerobic digestion without separation of the pretreated biomass was favored, in almost all cases. A preliminary energy balance and economic assessment indicated that the process could be sustainable, leading to a positive net heat energy only when using a more concentrated pretreated slurry (i.e., 20% organic loading), or when applying NaOH pretreatment at a lower chemical loading.